CAR-T cells dual-target CD123 and NKG2DLs to eradicate AML cells and selectively target immunosuppressive cells - Xin Jin; Danni Xie; Rui Sun; Wenyi Lu; Xia Xiao; Yibing Yu; Juanxia Meng; Mingfeng Zhao (OncoImmunology)
Chimeric antigen receptor (CAR)-T cells have not made significant progress in the treatment of acute myeloid leukemia (AML) in earlyclinical studies. This lack of progress could be attributed in part to the immunosuppressive microenvironment of AML, such as monocyte-like myeloid-derived suppressor cells (M-MDSCs) and alternatively activated macrophages (M2 cells), which can inhibit the antitumor activity of CAR-T cells. Furthermore, AML cells are usually heterogeneous, and single-target CAR-T cells may not be able to eliminate all AML cells, leading to disease relapse. CD123 and NKG2D ligands (NKG2DLs) are commonly used targets for CAR-T therapy of AML, and M-MDSCs and M2 cells express both antigens. We developed dual-targeted CAR-T (123NL CAR-T) cells targeting CD123 and NKG2DL by various structural optimization screens. Our study reveals that 123NL CAR-T cells eradicate AML cells and selectively target immunosuppressive cells. A highly compact marker/suicide gene, RQR8, which binds targeting epitopes of CD34 and CD20 antigens, was also incorporated in front of the CAR structure. The binding of Rituximab to RQR8 leads to the elimination of 123NL CAR-T cells and cessation of their cytotoxicity. In conclusion, we successfully developed dual effects of 123NL CAR-T cells against tumor cells and immunosuppressive cells, which can avoid target escape and resist the effects of immunosuppressive microenvironment.